INFECTION PREVENTION AND CONTROL AWARENESS, ATTITUDES, AND PRACTICES AMONG HEALTHCARE PROFESSIONALS IN SOUTH INDIA - Thazha, Suhas K; Cruz, Jonas Preposi; Alquwez, Nahed; Scaria, Bibin; Rengan, Sameesh S; Almazan, Joseph U (Journal of Infection in Developing Countries, 2022)
Introduction: Infection is a key challenge in healthcare settings around the world. Healthcare professionals (HCPs), including medical laboratory technologists (MLTs) and nurses, are at risk of infection because they are in close contact with infected patients. This investigation was conducted to evaluate the awareness, attitude, and practices of Infection Prevention Control (IPC) among HCPs working in private tertiary hospitals in two states in South India. Methodology: This quantitative study surveyed 571 HCPs in southern India. In September 2021, an online survey was used to collect data on the respondents’ demographic and IPC-related variables, as well as their awareness, attitudes, and practices of IPC. Results: The survey revealed high level of awareness, positive attitudes, and good IPC practices. Among the IPC practices, “changing gloves between contacts with different patients” was the most often practiced and “washing hands after removal of gloves” was the least practiced. Being a nurse, being older, finishing a graduate program, attending a risk assessment training, having sufficient Personal Protective Equipment (PPE) at work, and being aware of the safety guidelines were associated with better awareness. Being a nurse, being older, and holding a diploma were associated with more positive attitudes. Being MLT, attending risk assessment training, having sufficient PPE at work, and being aware of the safety guidelines were associated with better IPC practices. Conclusions: Measures to sustain the high awareness, positive attitudes, and good IPC practices by dealing with the factors associated with these variables identified in this study must be planned and implemented.
Keywords: Type of access: Open Access; Healthcare; infection; medical laboratory technologist; nurses; prevention